1999
DOI: 10.1021/jp984136j
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Scattering Study on Dynamics of Water Molecules in MCM-41

Abstract: The dynamics of water molecules confined in MCM-41 was investigated by quasi-elastic neutron scattering. The measurement was performed for three water-filled MCM-41 samples with different pore sizes in the temperature range 200-300 K. The spectra were analyzed by using a model employed by Teixeria et al. in a study for bulk water. This model is composed of two motions of water molecules: rotational and translational diffusions. For the translational diffusion, water molecules in MCM-41 are, on the whole, less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
206
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(235 citation statements)
references
References 10 publications
23
206
0
Order By: Relevance
“…The success (even for pore diameters as low as 1 nm) of this very simple core-shell conceptual model is remarkable in view of the fact that the actual decrease in water mobility near hydrophilic surfaces occurs gradually over two or three water layers and that the first water layer is not really and MD simulation studies 38,43 , but it supports recent MD simulation results by Lerbret et al 37 . Our results on water diffusion are consistent with QENS data 32,96,97 (yielding a measure of confidence in the quality of our MD simulations) and can be described with a very simple "core-shell" conceptual model on which the first water monolayer is immobile on diffusive time scales while the rest of the pore water diffuses as fast as bulk liquid water.…”
Section: Water Density Distributionsupporting
confidence: 87%
See 2 more Smart Citations
“…The success (even for pore diameters as low as 1 nm) of this very simple core-shell conceptual model is remarkable in view of the fact that the actual decrease in water mobility near hydrophilic surfaces occurs gradually over two or three water layers and that the first water layer is not really and MD simulation studies 38,43 , but it supports recent MD simulation results by Lerbret et al 37 . Our results on water diffusion are consistent with QENS data 32,96,97 (yielding a measure of confidence in the quality of our MD simulations) and can be described with a very simple "core-shell" conceptual model on which the first water monolayer is immobile on diffusive time scales while the rest of the pore water diffuses as fast as bulk liquid water.…”
Section: Water Density Distributionsupporting
confidence: 87%
“…4 by calculating the slope of MSD(τ) from τ = 2 to 10 ps and by using a MSD(τ) function calculated either in the xy plane or in the z direction, whichever was parallel to the nearest surface. Our predicted D nanopore values are compared in Figure 8 with experimental results obtained by quasi-elastic neutron scattering (QENS) 32,96,97 . Most models used to interpret QENS data treat a small portion of the pore water as immobile.…”
Section: Water Density Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23][24][25] The slowing down of both rotational and/or translational motions of confined water molecules has been also verified to be promoted with decreasing pore sizes and temperatures. [26][27][28][29] These results have suggested that the specific hydrogen bonding network of water layer on surfaces differing from bulk water, i.e., the adsorbed water phase, is responsible for causing the freezing behavior of confined water in the supercooled state.…”
Section: Introductionmentioning
confidence: 98%
“…Quasi-elastic neutron scattering measurements demonstrated the strong confinement effect on translational diffusion of water molecules to decrease, while rotational motion was not affected remarkably. 37 Neutron spin echo analysis, however, indicated clear difference in dynamic nature between monolayer water and central bulky water in the pore. 20 Poor interconnection between both phases has been substantiated by DSC analysis of freezing-melting of pore water.…”
Section: -9mentioning
confidence: 97%